1. The problem statement, all variables and given/known data Find a power series for the function, centered at c, and determine the interval of convergence. 2. Relevant equations g(x) = 2 / (1-x^2) , c=0 3. The attempt at a solution 2 / (1+x)(1-x) = 1/(1+x) + 1/(1-x) 1/(1-(-x)) => Sum [(-1)^n (x^n)], n=0 to infinity. Converges when abs(x) < 1, (-1,1) 1/(1-x) => Sum x^n, n=0 to infinity. Converges when abs(x) < 1, (-1,1) So, 2/(1-x^2) = Sum[(-1)^n + 1]x^n, n=0 to infinity. OK, here's the part that is probably SO simple, but I'm just not seeing it. The book shows the series above, Sum[(-1)^n + 1]x^n, n=0 to infinity is then equal to: Sum 2x^(2n), n=0 to infinity. How do you do that last simplification? Sorry for such a simple question, but I'm stuck. :) Also, the book has the interval of convergence for the series as abs(x^2)<1 or (1,1), which I'm pretty sure is just a typo. It should be (-1,1), right?